2022
DOI: 10.3390/en15186622
|View full text |Cite
|
Sign up to set email alerts
|

Essence of Thermal Analysis to Assess Biodiesel Combustion Performance

Abstract: The combustion phenomena are always complex in nature due to the involvement of complex series and parallel reactions. There are various methods that are involved in analyzing combustion phenomena. Viscosity is the first and foremost factor that acts as the DNA of fuel. By evaluating the viscosity, it is possible initially to understand the combustion phenomena. Thermophysical and transport properties are helpful during the intensification of the combustion process. Combustion experiments are economically infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Furthermore, biodiesel can be mixed with diesel and used in diesel engines in any proportion. Although biodiesel might cause a small problem in liquidity under low-temperature conditions, it is still a good choice for reducing emissions under cold start conditions of diesel engines [40,41].…”
Section: Biodiesel Utilizationmentioning
confidence: 99%
“…Furthermore, biodiesel can be mixed with diesel and used in diesel engines in any proportion. Although biodiesel might cause a small problem in liquidity under low-temperature conditions, it is still a good choice for reducing emissions under cold start conditions of diesel engines [40,41].…”
Section: Biodiesel Utilizationmentioning
confidence: 99%
“…30 So far, most researchers have concentrated on coal combustion phenomena, with very few studies done on liquid fuels, particularly biodiesel combustion analysis. Atgur et al 31 recently reviewed the literature on Thermogravitometry analysis (TGA) and differential scanning calorimetry (DSC) to analyze heat flow, enthalpy, and thermal stability. They reported that the B20 blend has a high enthalpy, higher thermal stability, and a lower combustion peak temperature, as well as an enhanced combustion index and combustion intensity that is virtually similar to diesel.…”
Section: Introductionmentioning
confidence: 99%